Exploring variation in leaf mass per area (LMA) from leaf to cell: An anatomical analysis of 26 woody species2. Issue 10 (1st October 2013) - Villar, Rafael; Ruiz‐Robleto, Jeannete; Ubera, José Luis; Poorter, Hendrik
Abstract : Premise of the study: Plant species differ widely in the leaf biomass invested per unit area (LMA). LMA can be explained by variation in leaf thickness and/or density, both of which are influenced by anatomical tissue composition. The aim of this study is to quantify the anatomical characteristics that underlie variation in LMA in a range of woody species. Methods: Twenty‐six woody species, forming 13 species pairs with a deciduous and evergreen species from the same genus or family, were grown in a glasshouse. The youngest full‐grown leaves were analyzed for LMA and morpho‐anatomical characteristics at leaf, tissue, and cell level. Key Results: Considered over all species studied, leaf thickness and density were equally important to explain the variation in LMA, but the class difference between deciduous and evergreen species was mainly determined by thickness, whereas variation within each group was largely due to density. Evergreens had thicker leaves, predominantly caused by a larger volume of mesophyll and air spaces, whereas the higher leaf density within each group was due to a lower proportion of epidermis and air spaces, and overall smaller cells. Conclusions: The anatomical basis for variation in LMA in woody species depends on the contrast made. Higher LMA in evergreens is mainly due to a greater leaf thickness, caused by a larger volume of mesophyll and air spaces. Within deciduous species and evergreens, higher LMA is caused by a higher density, due to higher volumetric fractions of mesophyll and lower fractions of air spaces and epidermis.